Incidence, predictive factors and impacts of acute kidney injury in cirrhotic patients hospitalized for cellulitis. (12th September 2017) - Garcia Garcia de Paredes, Ana; Tellez, Luis; Rodriguez‐Gandia, Miguel Angel; Martinez, Javier; Rodriguez de Santiago, Enrique; Aguilera Castro, Lara; Gea, Francisco; Albillos, Agustín
Abstract: Background & Aims: Cellulitis is a common infection in patients with cirrhosis but its impact on progression of liver disease has been hardly addressed. This study examines the incidence of acute kidney injury (AKI), predictive factors and its impacts on mortality in cirrhotic patients hospitalized for cellulitis. Methods: Retrospective data from cirrhotic patients hospitalized for cellulitis over the period January 2006 to September 2015 were analysed. AKI was defined according to revised criteria of the International Club of Ascites. Results: A total of 101 episodes of cellulitis were examined (70.3% men; mean age 60.6 ± 13.6 years). Of patients, 27% met criteria for acute on chronic liver failure (ACLF) (grade 1: 63%; grade 2: 22%; grade 3: 15%). AKI was recorded in 50.5% (type 1: 67%; type 2: 19%; type 3: 14%). AKI was present on admission in 21 of the 51 patients (41%) who developed it. In the remaining 30 patients (59%), AKI appeared during hospitalization and its development was associated with a MELD score >14 (70% vs 30%, P =.024). In‐hospital mortality was 10% and all patients who died had AKI. A high MELD score on admission, AKI and ACLF were associated with in‐hospital mortality ( P <.05). One‐month transplant‐free survival was 84% (70% vs 98% in patients with and without AKI, P =.001). Conclusions: In cirrhotic patients, cellulitis is a serious infection that often leads to AKI and ACLF. AKI is a strong predictor of mortality in this setting.